2017
DOI: 10.1074/mcp.m116.061804
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Biology of the Human Malaria Parasite Revealed from the Proteomes of Mature Male and Female Gametocytes

Abstract: The gametocytes of the malaria parasites are obligate for perpetuating the parasite's life cycle through mosquitoes, but the sex-specific biology of gametocytes is poorly understood. We generated a transgenic line in the human malaria parasite Plasmodium falciparum, which allowed us to accurately separate male and female gametocytes by flow cytometry. In-depth analysis of the proteomes by liquid chromatography-tandem mass spectrometry identified 1244 and 1387 proteins in mature male and female gametocytes, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 78 publications
0
44
0
Order By: Relevance
“…Three proteomic studies on separated female and male gametocytes have been published, one in P. berghei [ 8 ] and two in P. falciparum [ 12 , 13 ]. Two of these studies compared female and male gametocytes to the precursor asexual stages, allowing identification of female- and male-upregulated proteins [ 8 , 12 ]. There has been one previous transcriptomic analysis on separated female and male gametocytes, in P. falciparum , where proteomic data was also generated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three proteomic studies on separated female and male gametocytes have been published, one in P. berghei [ 8 ] and two in P. falciparum [ 12 , 13 ]. Two of these studies compared female and male gametocytes to the precursor asexual stages, allowing identification of female- and male-upregulated proteins [ 8 , 12 ]. There has been one previous transcriptomic analysis on separated female and male gametocytes, in P. falciparum , where proteomic data was also generated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further identify a number of proteins as gametocyte- specific even though they had been reported as asexual by previous studies (Fig 4B). A recent proteomics study of male and female Pf gametocytes [33], not included in our original analysis, was used to test the robustness of our scores. When we included this data set in our final Bayesian proteomics scores, both gametocyte scores and gene ranks before and after addition of this data set were highly correlated (Pearson’s r=0.997 and Spearman’s rho=0.995, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Our approach suggests that the currently available MS data is sufficiently comprehensive to identify stage specific proteins when analysed in an integrative approach. We examined this directly by incorporating a new Pf gametocyte MS study [33] in our scoring. The authors reported 44 new gametocyte-specific proteins that were not reported by earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of the proteomic data from the gametocyte stage to the ookinete stage provides unprecedented opportunities for TBV antigen discovery (31)(32)(33)(34). In silico screening of TBV candidates using filters for potential surface localization and exclusive expression in sexual stages may yield very useful results worthy of future pursuance (35).…”
Section: Discussionmentioning
confidence: 99%